2018
DOI: 10.1167/tvst.7.5.22
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Static and Kinetic Perimetry Results are Eliminated in Retinal Disease when Psychophysical Procedures are Equated

Abstract: PurposeWe tested the hypothesis that clinical statokinetic dissociation (SKD, defined as the difference in sensitivity to static and kinetic stimuli) at the scotoma border in retinal disease is due to individual criterion bias and that SKD can be eliminated by equating the psychophysical procedures for testing static and kinetic stimulus detection.MethodsSix subjects with glaucoma and six with retinitis pigmentosa (RP) were tested. Clinical procedures (standard automated perimetry [SAP] and manual kinetic peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 49 publications
(70 reference statements)
1
24
0
Order By: Relevance
“…34 Starting with an age-corrected sensitivity value (rather than 25 dB) at the 4 seeding points introduces significant uncertainty. 21,22,48 Consequently, this may alter response criterion, such that a more intense stimulus is required before the subject indicates a response. This is further complicated by having only 1 reversal for the staircase, which finally manifests as higher seeding point errors using SFR because there is no opportunity to reorient to the actual sensitivity.…”
Section: Modifications To Sfr and Low Test Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…34 Starting with an age-corrected sensitivity value (rather than 25 dB) at the 4 seeding points introduces significant uncertainty. 21,22,48 Consequently, this may alter response criterion, such that a more intense stimulus is required before the subject indicates a response. This is further complicated by having only 1 reversal for the staircase, which finally manifests as higher seeding point errors using SFR because there is no opportunity to reorient to the actual sensitivity.…”
Section: Modifications To Sfr and Low Test Reliabilitymentioning
confidence: 99%
“…[10][11][12][13] One significant problem with clinical perimetry is the variability in sensitivity measurement, 14 particularly in conditions of disease [15][16][17] that may stem from a number of causes. [18][19][20][21][22] In the face of known issues with variability within and between tests, there has been a paradigm shift towards conducting more visual field tests. [23][24][25] Specifically, the concept of frontloading visual fields has been recommended at a baseline examination and at follow-up in order to minimize variability to maximize the detection of progressive loss.…”
mentioning
confidence: 99%
“…Nonetheless, sources of variability, error and discordance in clinical tests have been attributed to the imperfect nature of the psychophysical tasks often performed in clinical practice. For example, we have shown previously that discordance between retinal structure and resultant visual perception using different perimetric techniques can be due to the nature of the psychophysical task 23,32 . Similarly, issues regarding visual attention and uncertainty have contributed to inaccuracies in threshold determination under conditions of disease 33 .…”
Section: Discussionmentioning
confidence: 99%
“…This limits responses such as abstaining (the yes-no response in static perimetry) and those borne from criterion bias as modelled by Signal Detection Theory 21 . We have previously illustrated the use of this psychophysical method for eliminating the phenomenon of statokinetic dissociation [22][23][24] .…”
Section: Design Of the Line Sag Test (Lst)mentioning
confidence: 99%
“…We have recently shown that a major source of test variability can be attributed to psychophysical technique employed for functional testing: whether the task is subjective or relatively more objective in which subjective factors such as response criterion are minimized. Subjective psychophysical tasks are confounded by the contribution of individual variability not necessarily attributable to the state of the underlying anatomical substrate (Phu et al, 2016a, 2018b). Although approaches to minimize subjective bias in laboratory-based psychophysical tasks have been well-established (Green and Swets, 1973), such techniques have not been widely adopted in clinical techniques.…”
Section: Introductionmentioning
confidence: 99%